EUGENOL AS POTENTIAL MEDICINEREVIEW - R, Akshaya.; somasundaram, Jayalakshmi; A.K., Anjali (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to evaluate the abutment teeth selection in fixed partial denture (FPD) done by undergraduate students. For this, eugenol is a naturally occurring phenolic molecule that is used in dentistry. Eugenol is also used as a topical anesthetic agent in dentistry. Moreover, it has many pharmacological effects, like anesthetic and analgesic action in dentistry, and also antibacterial and antioxidant effects. Eugenol and thymol were found to possess general anesthetic properties. Since it is a phytochemical constituent, it exhibits highly potent anticancer activities that have been attributed to their effect on multiple signalling and apoptotic pathways. It illustrates potent antibacterial potential against the numerous strains of gram-positive and gram-negative bacteria. Eugenol damages the cell membrane and cell wall, which then induces cell lysis in gram-positive and gram-negative bacteria. It is also used as an irritant, sensitizer, flavoring agent, and root canal medicament in dentistry. Clove oil or eugenol can be used as a local anesthetic and also used as an anesthetic agent in several fish species. In this review study, an elaborate role of eugenol as a potential medicine is required. The review of the scientific literature was done in the preparation of the manuscript. The systems and databases were searched for relevant articles from PubMed and Google Scholar. Databases of individual journals were searched for keywords in this review. The aim of this study is to analyze the role of eugenol as potential medicine . The published article was selected from the years 1980 to 2020. In this review, 47 articles were reviewed. Hence, future research should be aimed at identifying different activities of eugenol.